Goodvertising as a Paradigmatic Change in Contemporary Advertising and Corporate Strategy - Pavol Minár (Communication Today, 2025)
One of the latest and very important trends in contemporary advertising is ‘goodvertising’, i.e. the inclination of brands to communicate about topics of goodness for the whole of society, and even on social change. Those topics are not directly related to their business strategies in the strict sense of the term. The companies, corporations and businesspeople behind these brands are making their advertising say that they are interested in something more than just sales curves. Goodvertising expresses a new type of marketing and branding: cause marketing and ‘brands that care’. This is the sign of great changes underway in corporate business and communication strategies. The article is based on an assumption that these changes have been the reaction to the generation of so-called Millennials and their lifestyles and preferences. This is a generation which has also brought – along with its perception of the world – a complex change in the economic as well as cultural setup of society as a whole. Millennials demand ‘purpose’ from companies and corporations, and therefore prefer brands that care. This is the reason for the birth of goodvertising, as a brand’s statement on serious issues which affect society, often with the intention of changing the world and human thinking. In advertising, to which the metaphor of “mirror of the society” can be applied, the attempt to change the world is a matter of paradigmatic change which has the potential to bring about a fundamental re-definition of life, both in economic terms and in terms of culture and civilisation.